THE VALUE OF SUFISM IN THE CUCI MORI TRADITION OF THE PSHT PRAGAAN BRANCH: AN INTERPRETIVE ANTHROPOLOGICAL REVIEW CLIFFORD GEERTZ - Ach Badri Amien; Suhendri bin Hasan; Ahmad Solihin Sirojuddin; Musdalifa Musdalifa (Universitas Islam Negeri Mataram, 2026)
This study examines the ritual of washing the mori (ceremonial cloth) practiced by the Persaudaraan Setia Hati Terate (PSHT) Pragaan Branch during the month of Suro, focusing on its stages and symbolic meanings. Using in-depth observation and interviews with PSHT elders and members, the study identifies three ritual stages: preparation of ritual materials, washing the mori with water from seven springs and setaman flowers, and a closing communal prayer. Each stage symbolizes spiritual renewal, inner purification, and moral discipline. Drawing on Clifford Geertz’s anthropological perspective, the ritual is interpreted as a system of symbols reflecting Javanese-Islamic cultural knowledge. Thick description shows that the ritual functions not only as an annual tradition but also as a means of identity formation, reinforcing brotherhood, moral values, and the continuity of the organization’s cultural and religious ethos.